2018
DOI: 10.1590/0034-7167-2016-0530
|View full text |Cite
|
Sign up to set email alerts
|

Decline of mortality from cervical cancer

Abstract: Additional efforts towards maintaining early detection and health education programs and towards using therapeutic strategies of greater efficiency are needed, given that mortality due to this form of cancer is considered avoidable when diagnosed early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
1
1
Order By: Relevance
“…A database study showed a reduction in coefficients of mortality from CC among female residents of the city of Recife, the capital of the federal state of Pernambuco in Northeast Brazil. Our results demonstrate an increase in the mortality rate from CC, which is discordant because our number of deaths is from a wider geographical and population coverage [30].…”
Section: Discussioncontrasting
confidence: 49%
“…A database study showed a reduction in coefficients of mortality from CC among female residents of the city of Recife, the capital of the federal state of Pernambuco in Northeast Brazil. Our results demonstrate an increase in the mortality rate from CC, which is discordant because our number of deaths is from a wider geographical and population coverage [30].…”
Section: Discussioncontrasting
confidence: 49%
“…An American study shows that 54% of women with cervical cancer are diagnosed under 50 years of age, followed by women aged 50-69 years (33%) and with localized diseases (14) . In an ecological study of time series conducted in Brazil, it was observed that the risk of death from cervical cancer increases in women from 60 years of age (15) .…”
Section: Discussionmentioning
confidence: 99%
“…O câncer é a principal causa de morbilidade e mortalidade no mundo. A Agência Internacional de Pesquisa em Câncer (IARC), que faz parte da OMS, apontou que 14 milhões de novos casos foram notificados no ano de 2012, sendo cerca de 60% na África, Ásia, América Central e do Sul (Nascimento et al, 2018). Estima-se cerca de 600 mil casos novos registrados no Brasil por ano nos anos 2018-2019, sendo em sua maioria em estágio avançado da doença (INCA, 2018).…”
unclassified